An Introduction to Multiagent Systems - Wooldridge Michael (John Wiley & Sons, Ltd, 2002)
This book provides a comprehensive introduction to intelligent agents and multiagent systems, and assumes no specialist knowledge. Preface, Introduction, Intelligent Agents, Deductive Reasoning Agents, Practical Reasoning Agents, Reactive and Hybrid Agents, Multiagent Interactions, Reaching Agreements, Communication, Working Together, Methodologies, Applications, Logics for Multiagent Systems, Afterword, References, Index.